2011
DOI: 10.1038/nature10598
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear PKM2 regulates β-catenin transactivation upon EGFR activation

Abstract: SUMMARYThe embryonic pyruvate kinase M2 (PKM2) isoform is highly expressed in human cancer. In contrast to the established role of PKM2 in aerobic glycolysis or the Warburg effect 1,2,3 , its nonmetabolic functions remain elusive. Here we demonstrate that EGFR activation induces translocation of PKM2, but not PKM1, into the nucleus, where K433 of PKM2 binds to c-Srcphosphorylated Y333 of β-catenin. This interaction is required for both proteins to be recruited to the CCND1 promoter, leading to HDAC3 removal fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
907
8
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 866 publications
(964 citation statements)
references
References 26 publications
(35 reference statements)
31
907
8
2
Order By: Relevance
“…These events could in turn release β-catenin and into the cytoplasm and then into the nucleus, where it acts as a co-activator of T-cell and lymphoid enhancer factors (TCF/LEF) in the transcriptional activation of target genes (such as c-myc, snail-family members, cyclinD1 and Vimentin) involved in proliferation, invasion and tumor progression (Fang et al, 2007;Ji et al, 2009). Recent studies showed that EGF promoted glioblastoma cancer cell proliferation by increasing the expression of c-myc and cyclin D1, Which were regulated by the level of β-catenin phosphorylation at Tyr 333 residue (Yang et al, 2011). Our current results suggested that PI3K could phosphorylate β-catenin at Ser552 residue in a GSK3β-independent way upon EGFR activation, which upregulated the expression of snail and Vimentin, leading to HCC cell EMT and migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These events could in turn release β-catenin and into the cytoplasm and then into the nucleus, where it acts as a co-activator of T-cell and lymphoid enhancer factors (TCF/LEF) in the transcriptional activation of target genes (such as c-myc, snail-family members, cyclinD1 and Vimentin) involved in proliferation, invasion and tumor progression (Fang et al, 2007;Ji et al, 2009). Recent studies showed that EGF promoted glioblastoma cancer cell proliferation by increasing the expression of c-myc and cyclin D1, Which were regulated by the level of β-catenin phosphorylation at Tyr 333 residue (Yang et al, 2011). Our current results suggested that PI3K could phosphorylate β-catenin at Ser552 residue in a GSK3β-independent way upon EGFR activation, which upregulated the expression of snail and Vimentin, leading to HCC cell EMT and migration.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that EGF up-regulated β-catenin transcriptional activity via a Wntindependent mechanism. Next, we asked whether EGF affected phosphorylation of β-catenin, which has been shown to be positively correlated with its nuclear translocation and independent of Wnt signaling (Fang et al, 2007;Yang et al, 2011). Interestingly, treatment with EGF for 24 h induced phosphorylation of β-catenin at Ser552 and Tyr 333 in a concentration-dependent manner in SMMC-7721 cells ( Figure 3C).…”
Section: Both Pi3k and Erk Pathways Are Involved In Egfinduced β-Catementioning
confidence: 96%
See 1 more Smart Citation
“…Par exemple, les mutations activatrices de l'isocitrate déshydro-génase 1 dans des glioblastomes humains suggèrent que le contrôle métabolique est un élément clé de la carcinogenèse [3]. De même, PKM2 exerce un contrôle direct sur la progression du cycle cellulaire en activant la -caténine et participe ainsi à l'activation de la tumorigenèse induite par le facteur de croissance épidermique (EGF) [39]. Par ailleurs, les métabolites, tels que le NAD + et l'acétyl-CoA, produits en excès par une glycolyse accrue, influencent également l'activité d'enzymes responsables de modifications épigénétiques de la chromatine.…”
Section: Conclusion : L'effet Warburg Cause Ou Conséquence De La Carunclassified
“…In contrast with the constitutively active PKM1, PKM2 is allosterically regulated either as a dimer with low affinity for PEP or as a tetramer with high affinity for PEP (Mazurek et al, 2005). The oncogenic signal-mediated allosteric change of PKM2 leads to accumulation of various glycolytic metabolites for macromolecular biosynthesis to support cell growth, providing a selective growth advantage for tumor cells (Christofk et al, 2008a;2008b;Hitosugi et al, 2009;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%